Social exclusion influences conditioned fear acquisition and generalization: A mediating effect from the medial prefrontal cortex - H. Dou; Y. Lei; X. Cheng; J. Wang; PHT Leppänen (NeuroImage, 2020)
Fear acquisition and generalization play key roles in promoting the survival of mammals and contribute to anxiety disorders. While previous research has provided much evidence for the repercussions of social exclusion on mental health, how social exclusion affects fear acquisition and generalization has received scant attention. In our study, participants were divided into two groups according to two Cyberball paradigm conditions (exclusion/inclusion). Both groups underwent a Pavlovian conditioning paradigm, functional near-infrared spectroscopy (fNIRS), and skin conductance response (SCR) assessments. We aimed to determine the effects of social exclusion on fear acquisition and generalization and whether modulation of the medial prefrontal cortex (mPFC) mediates this relationship. Our results showed that socially excluded participants featured significantly higher and lower shock risk scores to safety stimuli (conditioned stimulus, CS-) and threatening stimuli (CS+), respectively, than did socially included subjects during fear acquisition. The exclusion group had increased skin conductance responses (SCRs) to CS and exhibited heightened shock risk and increased SCRs to generalized stimuli compared with the inclusion group. The fNIRS results demonstrated that the CS ​+ ​evoked larger oxy-Hb changes in the mPFC in the inclusion group than in the exclusion group during fear acquisition. Furthermore, the oxy-Hb of left mPFC of CS ​+ ​mediated the effect on the association between social exclusion and perceived risk of CS+ in the fear acquisition. Our results indicate that social exclusion impairs fear acquisition and generalization via the mediation of the mPFC and that social exclusion increases susceptibility to anxiety disorders through bias processing of fear discrimination in fear acquisition and generalization. By studying the role of social relationship in fear acquisition and generalization, our research provides new insights into the pathological mechanisms of anxiety disorder.